Comparative analysis of power augmentation in air bottoming cycles - Saghafifar, Mohammad; Poullikkas, Andreas (My University, 2017)
The air bottoming cycle (ABC) is a proposed plant configuration in which the steam turbine bottoming cycle in conventional combined power plants is replaced by another gas turbine cycle. Nevertheless, ABC's relatively low efficiency reduces the likelihood of having an ABC power plant in the near future. In this research work, steam injection in the topping cycle combustion chamber and supplementary firing are recommended to improve ABC's performance. Three different configurations of ABC, including simple ABC, ABC with steam injection, and ABC with supplementary firing, are investigated. A thermo-economic analysis is performed to study the effects of the proposed power augmentation approaches thermodynamically and economically. Moreover, optimisation is carried out with the objective of minimising the total cost of the plant for different configurations. Furthermore, a multi-objective optimisation is performed and the results are presented to further understand the trade-off between higher efficiency and lower operating cost.
Keywords: Αir bottoming cycle; Steam injection; Supplementary firing; Thermo-economicoptimisation